2018
DOI: 10.1016/j.jid.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Genes Related to Xenobiotic Metabolism in the Skin of Patients with Atopic Dermatitis but Not with Ichthyosis Vulgaris

Abstract: Previous transcriptome analyses underscored the importance of immunological and skin barrier abnormalities in atopic dermatitis (AD). We sought to identify pathogenic pathways involved in AD by comparing the transcriptomes of AD patients stratified for filaggrin (FLG)-null mutations to those of both healthy donors and patients with ichthyosis vulgaris. We applied RNA sequencing to analyze the whole transcriptome of nonlesional skin. We found that 607 genes (476 up-regulated and 131 down-regulated by >2-fold) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
1
31
0
3
Order By: Relevance
“…Tregs exposed to phenanthrene show decreased TGF‐β and IL‐10 and increased IL‐4, IL‐13, (p)STAT6 and GATA‐3 . It has recently been shown that repeated exposure to air pollution and to noxious molecules may promote AD . Thus, pollutants may contribute to AD also via their ability to affect Treg populations, especially by impeding their immunosuppressive capacity by causing them to redifferentiate into Th‐like cells that produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tregs exposed to phenanthrene show decreased TGF‐β and IL‐10 and increased IL‐4, IL‐13, (p)STAT6 and GATA‐3 . It has recently been shown that repeated exposure to air pollution and to noxious molecules may promote AD . Thus, pollutants may contribute to AD also via their ability to affect Treg populations, especially by impeding their immunosuppressive capacity by causing them to redifferentiate into Th‐like cells that produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, AD prevalence is relatively high, affecting 15%‐30% of children and 2%‐10% of adults. Notably, AD prevalence has markedly increased during the past 40 years, potentially because of a higher pollution burden …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Das Ziel der prämierten Arbeit war es, die molekulare Signatur der Haut von Patienten mit Atopischer Dermatitis mit und ohne Filaggrin Mutation sowie Ichthyosis vulgaris zu entschlüsseln, um somit die Rolle von Filaggrin in der Entstehung der Atopischen Dermatitis versus Ichthyosis vulgaris genauer definieren zu können. Zu diesem Zweck verwendeten die Autoren „Next Generation Sequencing“ um die Transkriptome von Hautproben von Kontrollpersonen und Patienten mit (i) Atopischer Dermatitis ohne Filaggrin Mutationen, (ii) Atopischer Dermatitis mit Filaggrin Mutationen, (iii) Ichthyosis Vulgaris sowie von Patienten mit (iiii) Ichthyosis Vulgaris und Atopischer Dermatitis zu vergleichen . Dabei wurde die überraschende Entdeckung gemacht, dass in der Atopischen Dermatitis – unabhängig vom Filaggrin Mutationsstatus – Gene, welche im Metabolismus von Xenobiotika eine entscheidende Rolle spielen, verstärkt exprimiert werden.…”
unclassified